Supplementation of growth enhancer on Ongole grade cattle: effects on nutrient utilization, and growth performance - Wara Pratitis Sabar Suprayogi; Susi Dwi Widyawati; Adi Ratriyanto; Agung Irawan (Universitas Sebelas Maret, 2022)
Objective: This experiment aimed to assess natural growth enhancers supplementation on nutrient metabolism and production performance of Ongole grade cattle.Methods: The solid growth enhancer (GE) was formulated to contain highly soluble energy sources (molasses), nitrogen (urea), bypass protein (dried-Leucaena leaves and soybean meal), polyunsaturated fatty acids (fish oil), phytonutrient-rich source (T. catappa), and mineral premix. In total, 25 Ongole grade cattle at 1-1.5 years in age averaged 150 ± 12 kg of initial body weight were distributed to receive five dietary treatments as follow: P0 = basal diet; P1 = P0 + 5 g/kg BW0.75 GE; P2 = P0 + 10 g/kg BW0.75 GE; P3 = P0 + 20 g/kg BW0.75 GE; P4 = PO + 30 g/kg BW0.75 GE, respectively, (5 replicates per treatment). The experiment lasted 10 months.Results: GE supplementation at 5g/kg BW0.75 (P1) significantly increased daily gain and final BW compared to P0 (P<0.05). Voluntary intake for dry matter, crude protein, and total digestible nutrient increased for cattle fed diets containing GE (P<0.05) compared to P0 but no difference among supplementary levels (P>0.05). Digestibility of DM and CF were significantly higher at P1 t (P<0.05) while N retention was highest on P1 and P2 and P0 was the lowest (P<0.05). Cattle fed with P1 and P2 treatments excreted higher allantoin and uric acid thus produced higher microbial protein synthesis than other treatments (P<0.05).Conclusions: In conclusion, dietary GE increased nutrient density of the ration and supplementation at 5g/kg BW0.75 could increase voluntary intake and nutrient utilization, and thus increased performance parameters of Ongole grade cattle.